A orientação educacional que ultrapassa os muros da escola - Milet, Rosa Maria Lepak (1990)
This work consists of reflexion and analysis of the role of the educational guide in Brasilian public school that attends the students of popular classes. It also presents analysis of processes of selectivity of the present day public school and its relation to the social crisis of the nation. In this picture, it evaluates the importance and need of the presence of educational guide in the school from the theoretical and practical study of options that constitute the basis of the work debated in congresses of guides and that define the profissional position of the category, in face of the questions that do not allow classes of entering in the school. The work distinguishes the two of educacional guidance present in the school the popular conceptions nowadays, evidencing the fundamental aspects of the practice of guides that actuate in the teaching municipal net in Rio de Janeiro. It also affirms the political and pedagogical i~ portance of the educational guidance in the school, introducing experiences that indicate ways of reformulating pedagogical practice through the daily life out of school of the student.